1986
DOI: 10.1021/jm00159a043
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active derivatives of gossypol: synthesis and antimalarial activities of peri-acylated gossylic nitriles

Abstract: A series of peri-acylated gossylic nitriles were synthesized from gossypol dioxime by treatment of the dioxime with the appropriate acid anhydride and its salt. The reaction pathway was elucidated by isolation and characterization of intermediates. Peri-acylated gossylic nitriles (acyl = acetyl, propionyl, butyryl, and valeryl) were compared with gossypol for activity against both chloroquine-sensitive and chloroquine-resistant strains of Plasmodium falciparum. The gossylic nitriles all retain activity, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 1 publication
2
90
0
Order By: Relevance
“…A large number of gossypol derivatives, such as Schiff's bases, esters, and ethers have been prepared. Several gossypol derivatives and analogs, such as compounds 3-6, possess activities such as antimalarial, anti-cancer, HIV (human immunodeficiency virus), and antiparasitic properties [31][32][33][34][35][36][37]. High throughput screening studies on a gossypol derivative 5 were performed in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of gossypol derivatives, such as Schiff's bases, esters, and ethers have been prepared. Several gossypol derivatives and analogs, such as compounds 3-6, possess activities such as antimalarial, anti-cancer, HIV (human immunodeficiency virus), and antiparasitic properties [31][32][33][34][35][36][37]. High throughput screening studies on a gossypol derivative 5 were performed in vivo and in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, inhibition of a crucial enzyme, like LDH, in the glycolytic pathway is a rational approach for the development of a novel antitheilerial drug that will have a different mode of action than the existing drugs. Determination of differences between plasmodial LDH and host LDH indicated that both enzymes are distinguishable in their structural and kinetic properties (VanderJagt et al 1981;Royer et al 1986;Makler and Hinrichs, 1993;Dunn et al 1996;Turgut-Balik et al 2001a). Insertion of five amino acids between residues S 108 -R 109 in the substrate specificity loop (101-109) is characteristic for the apicomplexan parasite LDHs cloned to date.…”
Section: Discussionmentioning
confidence: 99%
“…Gossypol is a polyphenolic binaphthyl disesquiterpene compound present in cottonseed oil. Its derivatives have been tested against PfLDH and reported to be strong inhibitors of the parasite enzyme (Royer et al 1986). However, the cytotoxicity of gossypol has stopped any further development with regard to PfLDH inhibition (Granchi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, gossypol has been showed to exhibit anti-tumor activities towards a wide range of tumors, such as Ehrlich ascites tumor cells [2], SW-13 adrenocortical carcinoma cells [3], hormone-dependent and hormone-independent breast carcinoma [4,5], colon carcinoma cell line HT-29 and LoVo [6], human pancreatic cancer cell line [7], prostate cancer cell lines [8], head and neck cancer cells [9,10]. In addition, many synthesized gossypol derivatives and analogues possess disease-inhibiting activities [11], as anti-parasitic [12,13], anti-malarial [14][15][16], anti-HIV [17][18][19] and anticancer [20][21][22][23]. Derivatives such as gossypol Schiff bases prepared by modifying gossypol's aldehyde groups were supposed to Open Access Natural Science reduce its host toxicity ( Figure 1) while retaining or enhancing its therapeutic effects [24].…”
Section: Introductionmentioning
confidence: 99%